Preparation and characterization of aspartic acid doped polypyrrole for the efficient removal of Cr(VI) from aqueous solution. (June 2016) - Amalraj, Augustine; Selvi, M. Kalai; Rajeswari, A.; Pius, Anitha
Graphical abstract: Highlights: Asp-PPy polymer composite was prepared and characterized for Cr(VI) removal. Adsorption capacity is highly dependent on pH. The maximum adsorption capacity is found to be 176.7 mg/g. The equilibrium adsorption data fit well to the Langmuir isotherm model. Asp-PPy can be reused four times without loss of its Cr(VI) removal efficiency. Abstract: A new aspartic acid doped polypyrrole (Asp-PPy) was prepared via in situ polymerization of pyrrole with aspartic acid for the removal of Cr(VI) from aqueous solutions. The prepared Asp-PPy was characterized using FT-IR, SEM with EDS, XRD, XPS and BET methods. The adsorption experiments were carried out in batch mode to optimize various parameters viz., contact time, pH, adsorbent dose, co-ions and temperature that influence the adsorption rate. Langmuir, Freundlich and Dubinin-Radushkevich adsorption isotherm models were applied to describe isotherm constants. Equilibrium data agreed well with the Langmuir isotherm model with maximum adsorption capacity of 176.7 mg/g. Thermodynamic studies revealed that the nature of adsorption is spontaneous and endothermic. The kinetic process demonstrates that the adsorption process follows pseudo-second-order and intra-particle diffusion models. The mechanism of Cr(VI) adsorption by Asp-PPy was governed by the ionic interaction between NH3 + of Asp and HCrO4 − ions. Asp-PPy can be reused successfully for the removal of Cr(VI) four times without loss of its removal efficiency. Asp-PPy can be a promising material to remove toxic Cr(VI) from the aqueous environment due to having high Cr(VI) capacity, good ion exchange property, non-toxic, environmental stability and low cost.